Effect of the alien invasive bivalve Corbicula fluminea on the nutrient dynamics under climate change scenarios. (1st May 2018) - Coelho, J.P.; Lillebø, A.I.; Crespo, D.; Leston, S.; Dolbeth, M.
Abstract: The main aim of this study was to evaluate the impact of the alien invasive bivalve Corbicula fluminea (Müller, 1774) in the nutrient dynamics of temperate estuarine systems (oligohaline areas) under climate change scenarios. The scenarios simulated shifts in climatic conditions, following salinity (0 or 5) and temperature (24 or 30 °C) changes, usual during drought and heat wave events. The effect of the individual size/age (different size classes with fixed biomass) and density (various densities of <1 cm clams) on the bioturbation-associated nutrient dynamics were also evaluated under an 18-day laboratory experimental setup. Results highlight the significant effect of C. fluminea on the ecosystem nutrient dynamics, enhancing the efflux of both phosphate and dissolved inorganic nitrogen (DIN) from the sediments to the water column. Both drought and heat wave events will have an impact on the DIN dynamics within C. fluminea colonized systems, favouring a higher NH4 -N efflux. The population structure of C. fluminea will have a decisive role on the impact of the species, with stronger nutrient effluxes associated with a predominantly juvenile population structure.